Pengaruh Kompensasi terhadap Kinerja Karyawan melalui Kepuasan Kerja sebagai Variabel Intervening di Bank Rakyat Indonesia Syariah Sidoarjo - Wulandari, Feni; Cahyono, Hendry (Universitas Negeri Surabaya, 2021)
Along with the times. The Islamic banking industry in Indonesia is growing rapidly. This makes competition between organizations or industries very fierce. The organization that already to be able to compete if the organization pays attention to the performance of its employees. This research aims to determine the effect of compensation on employee performance through job satisfaction of employees of Bank Rakyat Indonesia on Sidoarjo branch. This research design uses quantitative and causal associative with primary and secondary data sources. Classical Assumption Test and Path Analysis were chosen as data analysis methods. With this method, the results obtained have a significant direct effect of compensation on employee performance and indirect effect of compensation on employee performance through job satisfaction.